Selective formate separation using redox-active polyvinyl ferrocene-functionalized electrodes - POLAT, SEVGİ (My University, 2022)
Electrochemical separation of formate, a type of organic ion and the smallest carboxylate, has been heavily investigated because the separation challenges in the recovery of carboxylate products formed during electroreduction of CO2 and the purification of water, and in the current chemical and pharmaceutical industries. The objective of the present study was to use a response surface method involving the Box–Behnken design to investigate the fabrication process of polyvinyl ferrocene (PVF) / carbon nanotube (CNT) based electrodes for formate separation and to optimize these electrodes for a higher separation efficiency. First, the fabricated electrodes were characterized using cyclic voltammetry, X-ray diffraction, Raman spectroscopy, and scanning electron microscopy to determine their electrochemical, structural, and morphological properties. Then, Box–Behnken design with a selection of three effective independent variables was applied to determine the optimal conditions for the production of PVF/CNT electrodes with the maximum formate adsorption efficiency. Second-order polynomial equations were developed for the PVF/CNT ratio, sonication time, and ultrasonic amplitude to correlate the parameters. The statistical significance of the model and factors were evaluated using analysis of variance at a 95% confidence level. The optimization results showed that ultrasonic amplitude was the most effective parameter in comparison with other variables and operating at high ultrasonic amplitude and prolonged sonication duration negatively affected formate adsorption efficiency.